1995
DOI: 10.1128/iai.63.4.1211-1217.1995
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of mycobacterium-reactive gamma delta T cells by a subset of memory helper T cells

Abstract: Human ␥␦ T cells expressing the V␥9/V␦2 T-cell receptor have been previously found to proliferate in response to certain microorganisms and to expand throughout life, presumably because of extrathymic activation by foreign antigens. In vitro expansion of V␥9/V␦2 cells by mycobacteria has been previously shown to be dependent on accessory cells. In order to gain an insight into the mechanisms involved in the expansion of these cells, we have undertaken to identify the peripheral blood subset of cells on which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The experiments with fractionated TBe revealed that the components active on gd þ T cells were localized in the low molecular range, with two major peaks of bioactivity. The first peak, localized at a molecular mass of Ϸ14 kD, may correspond to the heat-stable, protease-sensitive antigen described by Boom et al [20], while the second peak, at a molecular mass < 6 kD, may represent the component(s) of the extract resistant to protease treatment, recently identified by several authors as the major mycobacterial stimulus for human gd þ T cells [8,30,34,35]. A complete digestion of the component active on gd þ T cells in SN2, together with the partial loss of gd þ T cell stimulatory activity of SN3 (extract from autoclaved and unwashed bacteria) in comparison with TBe, suggest that the protease-resistant component of the extract may be relatively less heat-stable than the protease-sensitive one which, instead, efficiently maintains its gd-stimulating capacity in the supernatant of autoclaved bacteria.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The experiments with fractionated TBe revealed that the components active on gd þ T cells were localized in the low molecular range, with two major peaks of bioactivity. The first peak, localized at a molecular mass of Ϸ14 kD, may correspond to the heat-stable, protease-sensitive antigen described by Boom et al [20], while the second peak, at a molecular mass < 6 kD, may represent the component(s) of the extract resistant to protease treatment, recently identified by several authors as the major mycobacterial stimulus for human gd þ T cells [8,30,34,35]. A complete digestion of the component active on gd þ T cells in SN2, together with the partial loss of gd þ T cell stimulatory activity of SN3 (extract from autoclaved and unwashed bacteria) in comparison with TBe, suggest that the protease-resistant component of the extract may be relatively less heat-stable than the protease-sensitive one which, instead, efficiently maintains its gd-stimulating capacity in the supernatant of autoclaved bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…The consequences of the reciprocal interaction(s) between ab þ and gd þ T cells are still a major question in the immune response to mycobacteria. While it seems that an efficient activation of gd þ T cells requires the interaction with ab þ T cells (via a cell-cell contact or soluble factors released by CD4 þ cells) [35,39], it is also possible that activated gd þ T cells may exhibit a regulatory function and affect the proliferative responses of ab þ T cells [5,40]. Increased proliferative responses of ab þ T cells in mice depleted of gd þ T cells have been described, suggesting a possible role for the gd þ T cells in the regulation of ab þ T cell activation in vivo [40].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, we demonstrate a requirement for memory CD4 T cells in the Vd2 cell response. [26][27][28] However, an important distinction is that previous studies have focussed primarily on the role of CD4 T cells in supporting Vd2 cell proliferation, whereas this is the first demonstration of their role in the initial activation of Vd2 cells, specifically effector responses such as IFN-g and cytotoxicity. For example, in a study by Pechhold et al, 28 Vd2 cells in co-culture with APCs upregulated CD25 in response to heat-killed Mycobacterium tuberculosis, but did not proliferate unless IL-2-producing CD4 T cells were present.…”
Section: Discussionmentioning
confidence: 99%
“…37 Young & Steinman 2 found g d cells present in cultures after stimulation with allogeneic dendritic cells implying that g d cells were replicating in response to the dendritic cells. Furthermore, dendritic cells, but not monocytes, have been shown to stimulate allogeneic 5 but not autologous 38 g d T cells from human blood and this response was blocked by anti-MHC class II mAb as well as mAb to CD2, CD3, CD28, CD11a and CD80. Thus, it has been proposed that a significant proportion of g d T cells express CD28, that these populations are stimulated by dendritic cells and may recognize foreign peptide in the context of MHC class I or II.…”
mentioning
confidence: 99%